An Efficient Protocol for Palladium N‐Heterocyclic Carbene‐Catalysed Suzuki‐Miyaura Reaction at room temperature. Issue 20 (18th July 2017) - Akkoç, Mitat; İmik, Fatma and Yaşar, Sedat and Dorcet, Vincent and Roisnel, Thiery and Bruneau, Christian and Özdemir, İsmail
Abstract: The palladium‐ N ‐heterocyclic carbene complexes have been synthesised from 1, 3‐bis‐(N‐alkyl)benzimidazolium salts and catalytic activity of complexes have been tested on Suzuki‐Miyaura coupling reaction for aryl bromides with substituted arylboronic acids at room temperature in i‐P rOH/water. Structural characterisation of palladium complex2 b was determined by x‐ray crystallography. A convenient and effective protocol has been evolved that has several superior advantages, including very low catalyst loading, vide range of substrate tolerance, excellent yields, room temperature, totally green solvents, short reaction times, up to 59750 h −1 TOF (Turn Over Frequency) value with aryl bromide substrates and very simple procedure. Abstract : The palladium‐NHC complex has been synthesized from 1, 3‐bis‐(N‐alkyl)benzimidazolium salts and catalytic activity of complexes has been tested on Suzuki‐Miyaura coupling reaction for aryl bromides at room temperature in i‐P rOH/water.